Anti-Inflammatory Effect Of Moringa Oleifera And Vitamin D On Articular Cartilage Degradation In Arthritic Rat Model: A Comparative Study - Shahid, Ayesha; Shabana Ali; Tayyaba Qureshi; Irum Zakria; Kaukab Anjum; Nomanna (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the anti-inflammatory effects of Moringa Oleifera and Vitamin D on articular cartilage degradation in the formalin-induced arthritis rat model.Study Design: Laboratory based experimental study Its lab based experimental study in which the effects of two drugs are compared there is no term comparativePlace and Duration of Study: Conducted in collaboration with the National Institute of Health (NIH) and the Department of Anatomy at Islamic International Medical College from September 2020 to September 2021.Methodology: as heading patients and method cannot be used here so written methodology Forty mature male Sprague Dawley rats were put into four groups of ten each. Group A, control and group B, negative control group (the untreated arthritic rat group were given standard rat diet. Male rats of treatment group C were given 4000IU/kg body weight of vitamin D and those of group D were given 500 mg/kg body weight of Moringa aqueous extract throughout the experiment via oral route. On the first and third days of experiment, all animals received subcutaneous injections of formaldehyde into their right paws except the control group A. The rat’s body weight was measured and recorded on day 1, 14 and 28. After the 28-day trial period, the right hind limb was removed, processed and stained with H&E for microscopic examination.  Results: The Moringa aqueous extract administration significantly reverted the articular cartilage damage when compared with vitamin D   Conclusion: Moringa Oleifera, a plant known for its anti-inflammatory properties, was